(untitled) (Journal of Forest and Livelihood, 2024)
Although the markets for NTFP is increasing, local harvesters have not been able to reap fair benefits. This is mainly because of non-conducive policy environment, imperfect market structure and complex socio-economic system that weakens the position of local communities in NTFP business. Citing the cases and figures of income disparity from NTFP trade in western Nepal, the author contends that policy is the overarching factor responsible for the situation. Any move to improve the situation should start from policy and provision of market and social services capable of elevating the position of local communities’ bargaining power and share of benefits.